Observation of WZ⁢𝛾 production in pp collisions at √s = 13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Junkermann, Thomas; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (Physical review letters, 2024)
This Letter reports the observation of 𝑊⁢𝑍⁢𝛾 production and a measurement of its cross section using 140.1±1.2 fb−1 of proton-proton collision data recorded at a center-of-mass energy of 13 TeV by the ATLAS detector at the Large Hadron Collider. The 𝑊⁢𝑍⁢𝛾 production cross section, with both the 𝑊 and 𝑍 bosons decaying leptonically, 𝑝⁢𝑝→𝑊⁢𝑍⁢𝛾→ℓ′±⁢𝜈⁢ℓ+⁢ℓ−⁢𝛾 (ℓ(′)=𝑒, 𝜇), is measured in a fiducial phase-space region defined such that the leptons and the photon have high transverse momentum and the photon is isolated. The cross section is found to be 2.01±0.30⁢(stat)±0.16⁢(syst) fb. The corresponding standard model predicted cross section calculated at next-to-leading order in perturbative quantum chromodynamics and at leading order in the electroweak coupling constant is 1.50±0.06 fb. The observed significance of the 𝑊⁢𝑍⁢𝛾 signal is 6.3⁢𝜎, compared with an expected significance of 5.0⁢𝜎.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
ATLAS Collaboration: G. Aad, L.M. Baltes, F. Bartels, M.M. Czurylo, S.J. Dittmeier, M. Dunford, S. Franchino, T. Junkermann, M. Klassen, T. Mkrtchyan, P.S. Ott, D.F. Rassloff, S. Rodriguez Bosca, C. Sauer, A. Schoening, H-C. Schultz-Coulon, V. Sothilingam, R. Stamen, P. Starovoitov, L. Vigani, S.M. Weber, M. Wessels, J. Zinsser [und viele weitere]
Gesehen am 21.10.2024